(untitled) (International Journal of Engineering and Computer Science, 2014)
The main aim of this project is to use a wireless technology for automobiles using GSM modem. The main scope of this project is to stop the automobile engine with the help of GSM modem when any person tries to steal the vehicle. When unauthorised person tries to unlock the door of car, then a programmable microcontroller 8051 gets an interrupt and order to GSM modem to send a SMS. GSM modem that stores owner’s number upon a miss call for the first time, sends an alert SMS to that authorized number. If owner reply to “stop the engine” then the control instruction is given to the microcontroller through interface that the output from which activates a relay driver to trip the relay that disconnects the ignition of the automobile resulting in stopping the vehicle.